Development of eating disorders in adolescence: a behavioral-analytic study - Teixeira, Bethania Serrão Peres; Coelho, Milena Vieira; Santos, Mikaele da Silva (Brazilian Journal of Science, 2022)
The following research aimed to identify the variables that influence the development of eating disorders (ED’s) in adolescence. Studies show that there is a higher prevalence of these in the female population and, therefore, it is defined that the research participants are female adolescents, aged between 12 and 18 years, accompanied at Adolescentro- Brasília, DF, Brazil by a multidisciplinary team. Data collection was carried out through a bibliographic survey, a study of medical records and a structured interview containing 25 questions with 14 adolescents. This is a descriptive study based on a qualitative approach, with data analyzed according to content analysis. The results showed that phylogenetic, ontogenetic (adolescent experience, behavioral patterns related to eating, stressful and traumatic contexts, satisfaction with body image and social support) and cultural (gender aspects and media influence) influence the development of eating disorders, and professionals need to investigate the variables in detail without neglecting any of them. It is concluded that it is important to build public policies to prevent eating disorders, insert the principle of equity when talking about gender differences and develop interventions that go beyond the individual context and permeate the collective.